Shradhanjali.com : new address for memories of our ancestors - Singh Ghura, Amarpreet K; Abhishek (London : Indian Institute of Management, Ahmedabad, 2016)
This case describes a situation in which Vivek Vyas and Vimal Popat conceive an idea to start an online obituary advertising platform while returning from a sales call. Vyas and Popat then discuss the ways to start the online obituary advertisement platform. The purpose of this case is to provide an opportunity to step into the shoes of Vyas and Popat and to explore and select the best possible option to offer an alternate solution to print obituary advertisement. The case provides the context for students to examine alternate options for the print obituary advertisement amidst lack of entrepreneurial experience of Vyas and Popat.
Originally published in Singh Ghura, A. K., & Abhishek (2016). Shradhanjali.com: New address for memories of our ancestors. BP0399. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Vyas, Vivek, -- active 2016.; Popat, Vimal; Shradhanjali.com.; Obituaries